The normalization trend of ventricular morphology after lateral ventricular tumor resection without additional diversion - Heyuan Jia; Zhixu Bie; Yehong Fang; Zhixian Gao; Xingchao Wang (Scientific Reports)
Abstract Intraventricular tumors frequently provoke alterations in ventricular morphology. This study aims to quantificational assess perioperative dynamic fluctuations in the cerebrospinal fluid (CSF) volume within the lateral ventricles of patients harboring lateral ventricular tumors. A retrospective review encompassing 90 patients who underwent surgical intervention for lateral ventricular tumors at our institution was undertaken. Comprehensive observations at multiple perioperative time points were conducted, and LVCV analyses were performed to delineate the longitudinal dynamic alterations in ventricular morphology. Additionally, LVCV measurements were juxtaposed with data from 19 healthy subjects to stratify patients into two cohorts: those exhibiting preoperative increased LVCV and those without such changes. After surgical excision of intraventricular tumors, alterations in LVCV were compared between these cohorts, with a factor analysis undertaken specifically among patients demonstrating increased LVCV to elucidate potential influencing variables. 40 patients (44.4%) diagnosed with intraventricular tumors presenting with enlarged preoperative LVCV [74.6 (49.3–101.8) cm3] compared with the normal subject group, and the LVCV demonstrated a significant postoperative [41.3 (27.6–67.5) cm3] reduction in 3 months (p < 0.001). Meanwhile, 50 patients (55.6%) without LVCV enlargement [14.5 (8.1–21.0) cm3] experienced a notable increase following surgery in 3 months [20.2 (14.1–33.3) cm3, p = 0.002]. Preoperative increased LVCV is an important factor leading to the increased LVCV postoperatively (p = 0.022, OR = 26.239), however, compared to healthy subjects, both groups exhibited a trend toward normalization of LVCV value postoperatively (p = 0.165, p = 0.072, respectively). Following appropriate surgical excision of the tumor, the preoperative increased LVCV associated with intraventricular tumors does not hinder the normalization trend of ventricular morphology. Not all ventricular dilation requires preventive long-term external ventricular drainage and aggressive ventriculoperitoneal shunt treatment.